Agronomic behavior of the turnip (Brassica napus L.) during the application of homeopathic medicines - Abasolo-Pacheco, Fernando; Ojeda-Silvera, Carlos Michel; Cervantes-Molina, Jonathan Enrique; Moran-Villacreses, Enma; Vera-Aviles, Daniel; Ganchozo-Mendoza, Enny; Mazón-Suástegui, José Manuel (REVISTA TERRA LATINOAMERICANA, 2020)
The production of the turnip (Brassica napus L.) in Ecuador, depends largely on the use of agrochemicals, whose indiscriminate use causes negative effects on the environment. Agricultural homeopathy has emerged as an ecological alternative to improve the health status of plants. In order to help improve the sustainable production of vegetables, the effect of two centesimal dynamics (7CH and 31CH) of three homeopathic medicines for human use was evaluated: Silicea terra (SiT), Natrum muriaticum (NaM) and Phosphoricum acidum (PhA ), on the germination, emergence and vegetative development of B. napus plants, applying a completely randomized 2×3+1 block design with three repetitions for the three stages of the crop. The variables evaluated during germination and emergence were: percentage of germination and emergence, length of stem and radicle, fresh weight of the aerial part and radicle, dry weight of the aerial part and radicle. The variables evaluated during vegetative development were: plant height, stem diameter, number of leaves, weight, leaf area and productive yield. Signif icant differences were recorded in all the variables and stages of development studied. The highest germination values corresponded to SiT-7CH and PhA-7CH (100%), surpassing the control group (83.5%). The PhA-7CH and NaM-31CH treatments stimulated stem growth in the germination stage (3.40 cm) and NaM-7CH root growth (4.07 cm) in the emergence stage. During the vegetative development, the plants with the highest production were those treated with NaM-7CH. The highest prof itability of the crop (71.33%), with a benef it / cost ratio of 1.7% was obtained with SiT-7CH. The results obtained suggest that agricultural homeopathy has potential in horticulture, since all treatments favorably influenced the response variables during germination, emergence and vegetative development of (Brassica napus L.).